PENGARUH KEBUDAYAAN MENYONTEK TERHADAP PERKEMBANGAN KEMANDIRIAN ANAK: UPAYA PEMBERANTASAN KEBIASAAN MENYONTEK DI LINGKUNGAN SEKOLAH - Awalia Marwah Suhandi; Triana Lestari (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Cheating is an act that is not good, but it is obligatory in the social environment, especially the school environment. various reasons why these actions are carried out is because of a lack of independence in learning. The culture of cheating with the development of independence has a correlation and a relationship between the two. The independence of a person is very much influenced by the social environment. The purpose of this research is to describe in detail whether there is a relationship with the culture of cheating with the development of children's independence and what efforts should be made to eradicate this culture. The results of the study revealed that of the 25 respondents had engaged in the habit of cheating, including assignments and tests. That is, in this case the child actually has not been able to achieve independence because it is said to be independent when someone can stand on their own feet and be able to solve problems. This research uses a quantitative method in the form of a survey with google form. The conclusion of the research is that the effort to eradicate cheating culture is the responsibility of oneself, parents, teachers, and the school environment to create a clean environment.